Why not use standard panel unit root test for testing PPP - Johan Lyhagen (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
In this paper we show the consequences of applying a panel unit root test when testing for a purchasing power parity relationship. The distribution of the tests investigated, including the IPS test of Im et al (1997), are influenced by a common stochastic trend which is usually not accounted for. The result is that the size tends to one with the number of cross-sections.
Keywords: C12; C22; C23; 330; Dynamic panels; Monte Carlo; Purchasing power parity; Kaufkraftparität; Unit Root Test; Theorie